2014
DOI: 10.1007/s00198-014-2677-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PTH(1–84) therapy on muscle function and quality of life in hypoparathyroidism: results from a randomized controlled trial

Abstract: Overall, our data do not support an immediate beneficial effect of PTH replacement therapy on muscle function or QoL. A high frequency of hypercalcemia among our patients may have compromised the potential beneficial effects of reversing the state of PTH insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 36 publications
4
122
1
7
Order By: Relevance
“…Whereas a cohort study showed improvement in QoL compared to baseline after treatment with rhPTH (52), an advantage in QoL of therapy with rhPTH compared to placebo could not be shown in a RCT (53). No studies reported on disability or sick leave.…”
Section: Study Endpointsmentioning
confidence: 91%
See 2 more Smart Citations
“…Whereas a cohort study showed improvement in QoL compared to baseline after treatment with rhPTH (52), an advantage in QoL of therapy with rhPTH compared to placebo could not be shown in a RCT (53). No studies reported on disability or sick leave.…”
Section: Study Endpointsmentioning
confidence: 91%
“…Severe vitamin D deficiency is associated with symptoms of myopathy, and patients with HypoPT often have neuromuscular complaints (4,38,53). To ensure that symptoms are not caused by low vitamin D levels, it seems reasonable to ensure an adequate vitamin D status (55).…”
Section: R26 We Suggest Aiming At An Adequate Vitamin D Status (4bbb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Рандоми зи ро ван-ное исследование применения ПТГ(1-84) в дозе 100 мкг/сут не выявило повышения мышечной силы и качества жизни у паци-ентов в течение 6 мес терапии [55]. Вместе с тем наиболее продолжительное пятилет-нее исследование показало повышение ка-чества жизни пациентов с гипопаратиреозом на фоне терапии ПТГ(1-84) в дозе 100 мкг 1 раз в два дня [56].…”
Section: рекомбинантный человеческий птг(1-84)unclassified
“…However, a significant beneficial effect of PTH-replacement therapy has so far not been documented in double-blinded randomized trials. The two largest double-blinded trials performed so far compared effects of 6 months of replacement therapy with PTH(1-84) with placebo [5,6]. In one of the trials, several participants, however, develop hypercalcemia in response to PTH(1-84) therapy, which may have blunted potential beneficial effects [5].…”
mentioning
confidence: 99%